ATP catabolism and bacterial succession in postmortem tissues of mud crab (Scylla paramamosain) and their roles in freshness. (May 2022) - Lin, Wei-Chuan; He, Yi-Min; Shi, Ce; Mu, Chang-Kao; Wang, Chun-Lin; Li, Rong-Hua; Ye, Yang-Fang
Graphical abstract: Highlights: Postmortem ATP catabolism changed in a tissue-dependent pattern in the mud crab. Muscle K value could be an optimal freshness indicator for mud crab. ATP catabolism was closely associated with microbiota in the muscle, but not in the hepatopancreas. Various bacterial community characteristics contributed to muscle K value. The mud crab of 4 h postmortem at room temperature remains edible. Abstract: The seafood microbiome is highly diverse and plays an essential role in the spoilage of seafood. Nevertheless, how such a diverse microbiome influences freshness of mud crab ( Scylla paramamosain ) remains unclear. Here we investigated the postmortem ATP catabolism and succession of the bacterial community in the hepatopancreas and muscle of S. paramamosain using a high-performance liquid chromatography method and 16S rRNA gene amplicon sequencing. Our results showed a tissue-dependent change in ATP catabolism determinized the differences in the changes of nucleotide freshness indices of hepatopancreas and muscle over postmortem time of mud crab. The muscle K value could be used as an optimal nucleotide freshness indicator for the freshness of mud crab, with a proposed threshold of 20%. From a microbiota perspective, a more significant bacterial community change was observed in the muscle than in the hepatopancreas. These changes could result in a close relationship between ATP and its catabolites and microbial taxa in the muscle. Moreover, Photobacterium, Peptostreptococcaceae, average path distance, OTU richness, and Shannon index of muscle bacterial community markedly contributed to K value. These findings suggest that the mud crab of 4 h postmortem at room temperature is still edible. Notably, the importance of microbial community composition and interaction for the spoilage of mud crab should be carefully considered.